2019
DOI: 10.1002/hpm.2748
|View full text |Cite
|
Sign up to set email alerts
|

Exploring trade‐offs between staffing levels and turnaround time in a pathology laboratory using discrete event simulation

Abstract: Summary Many health delivery services have required performance targets. Typically, these targets are presented as percentiles of patients to be seen within specified timeframes. These targets present hospital administrators with a resourcing problem complicated by conflicting objectives: How to minimize costs while maximizing throughput to achieve the performance targets? In this paper, we describe the use of a simulation model to evaluate the effect of changes to staff levels in a cytology department, invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In the last 2 decades there has been an explosive increase in the number of DES publications and a claimed diffusion of DES into healthcare 8 . It has been observed that the applications of DES are largely confined to specific health care units, with modelling of emergency departments the most popular setting 9,10 and many applications seeking to improve time‐ and efficiency‐related metrics 9,11 and cost‐effectiveness 12 . A recent systematic review found an increasing trend towards using DES in healthcare to address issues at an operational level, yet less than 10% of DES applications presented actual implementations following the modelling stage 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In the last 2 decades there has been an explosive increase in the number of DES publications and a claimed diffusion of DES into healthcare 8 . It has been observed that the applications of DES are largely confined to specific health care units, with modelling of emergency departments the most popular setting 9,10 and many applications seeking to improve time‐ and efficiency‐related metrics 9,11 and cost‐effectiveness 12 . A recent systematic review found an increasing trend towards using DES in healthcare to address issues at an operational level, yet less than 10% of DES applications presented actual implementations following the modelling stage 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding planning and capacity analysis, (Pinto et al 2015) defined the ideal number of beds for a Brazilian hospital. For the balancing of staff work (Reynolds et al 2011) applied the simulation to reduce the workload of an English pharmacy and (Pongjetanapong et al 2019) used the tool to evaluate the effect of changes to staff levels in a cytology department.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Authors revealed a growing interest on the use of Discrete Event Simulation (DES) as a performance analysis tool in 81% out of 254 selected papers. Recent studies have applied DES to situations where resource management scenarios exploration was essential to reduce operational costs and increase performance [2,14].…”
Section: Introductionmentioning
confidence: 99%